Monitoramento, análise e modelagem da qualidade da água na sub-bacia do Rio Poxim - Vasco, Anderson Nascimento do (2011)
In recent years, several studies have been conducted in order to investigate the problems related to reduced quality of water for public supply, recreation, irrigation, among others, leading to the identification of pollution sources and to develop proposals for its control. Improper use of water has caused serious problems especially in urban centers. The increasing contamination of water resources, caused by several sources, among which stand out the domestic sewage, industrial effluent and urban and agricultural diffuse load, is compromising the use of these resources for their various purposes. The Poxim River is an important source of Sergipe, which supplies a large number of farms and part of the capital Aracaju. Within this context, to understand and try to minimize the problem in a rational manner, we can tell, nowadays, with monitoring of water quality in watersheds and the development and application of tools that consider aspects of quantity and quality. The aim of this study was to monitor and analyze water quality through physical-chemical and microbiological contaminants in the sub-basin of Rio Poxim of different aspects of use and occupation and the possible interference that may cause these water resources, Besides using a computational tool AcquaNet able to simulate critical processes and scenarios for sub-basin, considering the framing parameters of water bodies, in accordance with Resolution 357/2005. To guarantee the water supplyment in amount and quality for agroecosystems and ecosystems associates to the river depends on the planning and management of the water resources that must be thought adopting the hydrographic basins as basic units of planning.